If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -8(2t + 6) = -112 Reorder the terms: -8(6 + 2t) = -112 (6 * -8 + 2t * -8) = -112 (-48 + -16t) = -112 Solving -48 + -16t = -112 Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '48' to each side of the equation. -48 + 48 + -16t = -112 + 48 Combine like terms: -48 + 48 = 0 0 + -16t = -112 + 48 -16t = -112 + 48 Combine like terms: -112 + 48 = -64 -16t = -64 Divide each side by '-16'. t = 4 Simplifying t = 4
| 16=y+2 | | 2(4x-2)=7x | | 8(s-10)=-124 | | 16a^2-24a+1=0 | | -4+2x=-8+16 | | 4(10+7x)=152 | | 2secx+8sinx=0 | | 10x^2+5x+11=9x^2-x+2 | | 4ax^2-4ax+a+c^2=0 | | 5x+7-11=26 | | cos5x=1/5 | | 4x-12=24+x | | 3x+x-2=2x+6 | | 4(2*-3)=36 | | 6p-3=2p+10 | | 11x-25=4x+3 | | x+2x=4700 | | x+2x=4000 | | 8(a-4)=16 | | 10x-131=3x-5 | | x=10x-4 | | 2x=3x+21 | | 3x+9=72-6 | | p=10p-4 | | -29.5-5b=3.5(7.5b-7) | | X/4=2x/5 | | -4.5k-8.5+6=24.5 | | 4x+2+4=30 | | (x-2)(6x+4)=0 | | 3(3+4x)=153 | | -5(6d-9.5)=-18.5 | | 5x+4=5x-8 |